Legal loopholes in a case of assisted reproduction. A law and economics approach - Carranza Chunga, Patricia (2022)
Peruvian case law has shown the legal loopholes in family procedure rules applicable to cases in which people use assisted reproduction techniques. A good example could be the legal consequences of taking legal action when a man refuses to acknowledge a child born out of wedlock who has been conceived by assisted reproduction without his consent and with the intervention of an anonymous sperm donor. In this regard, the active individual of the material relationship will face a dilemma where the State, through the judicial bodies, appears as the best suited to cover the high transaction costs resulting from the legal loopholes with regard to anonymous sperm donors. However, instead of finding a solution, people face unfair decisions triggering new situations that cause high transaction costs.